Efficacy of the Pilates versus general exercises versus educational workshops on neuromuscular parameters: A randomized controlled trial - Mendes Tozim, Beatriz [UNESP]; Thomaz de Aquino Nava, Guilherme [UNESP]; Zuliani Stroppa Marques, Ana Elisa [UNESP]; Tavella Navega, Marcelo [UNESP] (Elsevier, 2021)
Introduction: Muscle strength, flexibility and changes in muscle recruitment patterns are usually associated to low back pain (LBP). Physical exercises can reverse the adverse changes associated to LBP. Objectives: Compare Pilates, general exercises and educational workshop on muscle flexibility, strength and recruitment of the trunk extensor muscles in women with LBP. Methods: Forty-six women were randomly divided into Pilates group (PG, n = 16), general exercise group (GEG, n = 15), and educational group (EG, n = 15). This study sought to determine flexibility, muscle strength, and muscle recruitment of right (RIL), left (LIL) iliocostalis lumbar; right (RMU) and left (LMU) lumbar multifidus muscles. Both PG and GEG performed 16 exercise sessions, while EG attended 4 workshops. Statistical analysis used data sample from Shapiro-Wilk test, Pearson's correlation, multivariate analysis, mixed variance analysis, and Cohen's index. Results: Flexibility showed no differences (p > 0.05). Muscle strength increased in the intragroup analysis for PG (p = 0.003) and GEG (p = 0.002); however, the intergroup analysis presented no difference. Intergroup showed statistically significant differences for the recruitment of RMU in PG (p < 0.001). Intragroup analysis presented differences after interventions in PG for RIL (p = 0.001); in GEG for LIL (p = 0.005); and in EG for RIL (p = 0.007), LIL (p = 0.002) and RMU (p < 0.001). Conclusions: None of the groups showed flexibility improvements. PG and GEG increased muscle strength through intragroup analysis. Intergroup analysis showed an increase in recruitment of the RMU muscle in PG and all groups demonstrated significant improvements in the intragroup analysis.
Keywords: Aging; Articular; Electromyography; Exercise movement techniques; Low back pain; Physical therapy specialty; Range of motion